2020
DOI: 10.2147/dhps.s280442
|View full text |Cite
|
Sign up to set email alerts
|

<p>Evaluation of Surgical Antimicrobial Prophylaxis and Incidence of Surgical Site Infection at Borumeda Hospital, Northeast Ethiopia: Retrospective Cross-Sectional Study</p>

Abstract: Background: Surgical site infections are global healthcare problems. Although surgical site infections are preventable, they still cause significant morbidity, high death rates, and financial stress on national budgets and individual patients. Inappropriate uses of surgical antimicrobial prophylaxis are increasing and worsening patients' quality of life. This study determined the incidence and risk factors of surgical site infections. Methods: Institution-based retrospective cross-sectional study was conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 54 publications
0
11
1
Order By: Relevance
“…Abdominal surgery, which may involve multiple organs, was a serious stressor. DSSI was an important burden of the laparotomy, and the infections can spread to abdominal organs, and lead to shock, coma, and eventual death (25). DSSI were also notoriously difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
“…Abdominal surgery, which may involve multiple organs, was a serious stressor. DSSI was an important burden of the laparotomy, and the infections can spread to abdominal organs, and lead to shock, coma, and eventual death (25). DSSI were also notoriously difficult to treat.…”
Section: Discussionmentioning
confidence: 99%
“…1 However, lack of adherence to follow protocol for SAP is among one of the factors for irrational use. 6,7 Bacteria that become resistant to multiple antibiotics are often the result of incorrect or prolonged antibiotic use. 8 30% to 50% of antibiotics prescribed in hospitals are for postsurgical prophylaxis, and almost 30% to 90% of these regimens are unnecessary.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, a report from a meta-analysis study indicated that the estimated pooled occurrence of SSI in Ethiopia was 12.3% 11 . From an estimated 30–50% of the antimicrobials used for surgical prophylaxis in hospitals, 30–90% were inappropriate 17 . The use of surgical antimicrobial prophylaxis before any surgery in an appropriate way is an important measure to prevent SSI.…”
Section: Introductionmentioning
confidence: 99%
“…However inappropriate use of antimicrobial agents like inappropriate selection, timing, and duration are associated with an increase in the worldwide emergence of antimicrobial resistance, a major public health problem, and has a significant impact on treatment and outcomes. Moreover, there will be also increased risks of occurrence of surgical site infections, and adverse drug reactions thus strongly calling for the evaluation of SAP 15 , 17 .…”
Section: Introductionmentioning
confidence: 99%